Preparation of Infectious Cell-Free Herpes-Type Virus Associated with Marek's Disease - Cook, M. Katherine (1970)
Cell-free transmission of the herpes-type virus of Marek's disease was obtained by demineralized water treatment of infected chick embryo fibroblasts.